Business Intelligence as a Strategic Planning Tool in Healthcare Organizations: A Systems Integration Approach - Devika Rajhamundry (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
The integration of Business Intelligence (BI) in healthcare strategic planning has emerged as a critical factor in transforming raw data into actionable insights for executive decision-making. This article explores the comprehensive framework of BI implementation in healthcare organizations, addressing the challenges of integrating data from multiple specialized systems including Electronic Medical Records (EMR), physician credentialing, contracting management, revenue cycle operations, and quality assessment platforms. Through detailed analysis of data integration methodologies, analytical capabilities, and strategic applications, the article demonstrates how BI enables healthcare organizations to overcome system fragmentation and data silos while enhancing strategic decision-making processes. The article examines key use cases in patient volume analysis, quality management, and value-based care optimization, highlighting how integrated BI solutions contribute to improved operational efficiency and strategic planning. The article reveals significant improvements in organizational decision-making capabilities, demonstrated through enhanced patient acquisition metrics, quality management processes, and value-based care delivery. This comprehensive article on BI in healthcare strategic planning provides valuable insights for healthcare leaders seeking to leverage data analytics for organizational growth and operational excellence.